Certain theorems involving differential superordination and sandwich-type results - KAUR, Hardeep; BRAR, Richa; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
To obtain the main result of the present paper, we use the technique of differential superordination. As special cases of our main result, we obtain sufficient conditions for f ∈ A to be φ−like, parabolic φ−like, starlike, parabolic starlike, close-to-convex and uniform close-to-convex. We also obtain sandwich-type results regarding these functions. For demonstration of the results, we have plotted the images of open unit disk under certain functions using Mathematica 7.0. Mathematics Subject Classification (2010): 30C80, 30C45. Received 15 July 2022; Accepted 27 October 2022.